Dyslipidemia in pre- and post-menopausal women: a study of peri-urban Paundra Kshatriya women - Adak, Dipak Kumar; Bharali, Nitamoni; Biswas, Saptarshi; Bagchi, Niloy Kumar; Biswas, Tapas Kumar; Rao, Vadlamudi Raghavendra (Anthropological Review, 2023)
Dyslipidemia is an important risk factor of cardiovascular disease, whereas menopause is a decrease in ovarian follicular activity at the end of reproductive age of the women, which is significantly influenced by hormonal changes brought on by menopause’s impact on serum lipids. This study was undertaken among pre- and post-menopausal Paundra Kshatriya women in Sonarpur, South 24 Parganas, West Bengal, India in order to determine the prevalence of dyslipidemia. 142 adult Paundra Kshatriya women (n pre-menopausal women = 96; n post-menopausal women = 46) were selected from a peri-urban setting of Sonarpur, South 24 Parganas, West Bengal. Anthropometry and arterial pressure data were recorded. Blood samples were collected from study participants who were on 12 hours fasting. 19.79% of pre-menopausal women and 17.39% of post-menopausal women had normal levels of lipids. Prevalence of dyslipidemia was slightly higher (82.7%) among the post-menopausal women compared to pre-menopausal women (80.2%). While high LDL cholesterol emerged as one of the prime causes for dyslipidemia among pre-menopausal women, hypercholesterolemia emerged as one of the prime causes for dyslipidemia among post-menopausal women. Regression analysis revealed a significant impact of 3 factors in pre-menopausal women and impact of 6 factors in post-menopausal women. Though Paundra Kshatriya women maintain a relatively less stressful and high physical activity lifestyle, they exhibited high levels of lipid abnormalities. The peri-urban population is undergoing lifestyle and dietary changes due to a close proximity to the urban centre, Kolkata. Funding Anthropological Survey of India, Ministry of Culture, Government of India